ISOLASI DAN KARAKTERISASI SENYAWA METABOLIT SEKUNDER FRAKSI ETIL ASETAT DARI KULIT BATANG TUMBUHAN Bauhinia purpurea L - Ardiansyah Ardiansyah; Herdini Herdini; Abdullah Abdullah (Jurnal Pendidikan Kimia (JPKim), 2015)
Abstract Isolation and characterization secondary metabolite of ethyl acetate fraction from Bauhinia purpurea L stem bark has been conducted. Bauhinia purpurea L belonging to biggest family of flowering plant in Asia. This plant was choosed as study sample evidence remedy effect for some disease like ulcer, cough, tumor, puffing, and snakebite. Isolation conducted by extraction and chromatograph method. Extraction by maceration technique used non polar and semipolar solvent alternally, n-hexane, dichloromethane, and ethyl acetate. The extract separated by liquid vacuum, coloum, and flash chromatograph until obtained pure compound. The melting point of compound was determined by John-Fisher apparatus.The compound structure was determined by UV-Vis, IR, 13C-NMR spectroscopic.The compound spectroscopy data was compared with standard compound data.Extraction resulted n-hexane fraction, dichloromethane fraction, and ethyl acetate fraction. Separation of ethyl acetate fraction resulted white crystalline powder and has melting point 220-2210C. Evidence on spectroscopy data were estimated the compound was a stigmasterol glycoside.Key word : Bauhinia purpurea L; stem bark; ethyl acetate; stigmasterol glycoside